Potential role of serum hypoxia-inducible factor 1alpha as a biomarker of delayed cerebral ischemia and poor clinical outcome after human aneurysmal subarachnoid hemorrhage: A prospective, longitudinal, multicenter, and observational study - Cai, Ye-Yan; Zhuang, Yao-Kun; Wang, Wen-Jian; Jiang, Feng; Hu, Jie-Miao; Zhang, Xiao-Le; Zhang, Li-Xin; Lou, Xiao-Hui (Frontiers in Neurology, 2022)
Objective Hypoxia-inducible factor 1alpha (HIF-1α) functions as a crucial transcriptional mediator in hypoxic and ischemic brain response. We endeavored to assess the prognostic significance of serum HIF-1α in human aneurysmal subarachnoid hemorrhage (aSAH). Methods In this prospective, longitudinal, multicenter, and observational study of 257 patients with aSAH and 100 healthy controls, serum HIF-1α levels were quantified. Univariate analyses, followed by multivariate analyses, were performed to discern the relationship between serum HIF-1α levels and severity and delayed cerebral ischemia (DCI) plus poststroke 6-month poor outcome [extended Glasgow outcome scale (GOSE) scores of 1–4]. Predictive efficiency was determined under the receiver operating characteristic (ROC) curve. Results There were significantly increased serum HIF-lα levels after aSAH, in comparison to controls (median, 288.0 vs. 102.6 pg/ml; P < 0.001). Serum HIF-lα levels were independently correlated with Hunt–Hess scores [β, 78.376; 95% confidence interval (CI): 56.446–100.305; P = 0.001] and modified Fisher scores (β, 52.037; 95% CI: 23.461–80.614; P = 0.002). Serum HIF-lα levels displayed significant efficiency for discriminating DCI risk [area under ROC curve (AUC), 0.751; 95% CI: 0.687–0.815; P < 0.001] and poor outcome (AUC, 0.791; 95% CI: 0.736–0.846; P < 0.001). Using the Youden method, serum HIF-1α levels >229.3 pg/ml predicted the development of DCI with 92.3% sensitivity and 48.4% specificity and serum HIF-1α levels >384.0 pg/ml differentiated the risk of a poor prognosis with 71.4% sensitivity and 81.1% specificity. Serum HIF-1α levels >229.3 pg/ml were independently predictive of DCI [odds ratio (OR), 3.061; 95% CI: 1.045–8.965; P = 0.041] and serum HIF-1α levels >384.0 pg/ml were independently associated with a poor outcome (OR, 2.907; 95% CI: 1.403–6.024; P = 0.004). The DCI predictive ability of their combination was significantly superior to those of Hunt–Hess scores (AUC, 0.800; 95% CI: 0.745–0.855; P = 0.039) and modified Fisher scores (AUC, 0.784; 95% CI: 0.726–0.843; P = 0.004). The prognostic predictive ability of their combination substantially exceeded those of Hunt–Hess scores (AUC, 0.839; 95% CI: 0.791–0.886; P < 0.001) and modified Fisher scores (AUC, 0.844; 95% CI: 0.799–0.890; P < 0.001). Conclusion Elevated serum HIF-lα levels after aSAH, in independent correlation with stroke severity, were independently associated with DCI and 6-month poor outcome, substantializing serum HIF-lα as a potential prognostic biomarker of aSAH.